A Research on the Copies and the Author of the Philippine-Published Chinese Incunabula: Symbol of Faith - Yin, Xiao (Sinología hispánica. China Studies Review, 2019)
The Spanish Dominican Thomas Mayor published his Symbol of Faith in Chinese Language (Gewu Qiongli Bianlan) in 1607 Philippines. This article studies its present copies conserved in different libraries around the world indicated in earlier reports. It will also try to bring forward some new points of view about several debatable questions on the biography and the publications of this Spanish Dominican author through a thorough study of the archives about him dating up to the beginning of the seventeenth century, as well as all the discovered Philippine-published Chinese Incunabula in the present.